Capital Structure and Firm Efficiency: A Case of Pakistan - Akhtar, Tahir; Zahir, Ahmad; Tareq, Mohammad Ali; Rabbi, Fazle (Indian Journal of Finance, 2016)
This study investigated the effect of capital structure on firm performance using the agency cost hypothesis and reverse causality hypothesis. For the firms listed on the Karachi Stock Exchange under the textile industry, from 2008-2012, data envelopment analysis (DEA) was used to construct a frontier to measure firm efficiency. Efficiency risk hypothesis and franchise value hypothesis were tested to find out the effects between efficiency and leverage. The results suggested that ownership structure and leverage had a positive relationship (efficiency risk hypothesis) between them. The agency cost hypothesis supported the positive effect of leverage on efficiency. Convergence of interest, that is, concentrated ownership, had a positive effect on firm performance.